2019
DOI: 10.1038/s41598-019-45996-1
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the more myopic eye in anisometropia: the interplay of laterality, ocular dominance, and anisometropic magnitude

Abstract: This study reveals how, in a myopic anisometrope, the odds of an eye being more myopic are related to laterality, ocular dominance, and magnitude of anisometropia. In 193 subjects, objective refraction was performed with cycloplegia. Sighting, motor, and sensory dominance were determined with the hole-in-the-card test, convergence near-point test, continuous flashing technique, respectively. Multiple logistic regression was used for probability analysis. Seventy percent of the subjects had a right eye that was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…reported that the nondominant eye is more myopic in the anisometropia patients with interocular SE differences greater than 2.5 D. Wang et al [ 27 ] identified the nondominant eye had a tendency of higher refraction when SE anisometropia larger than 1.75 D in adults. However, the results on which eye is more myopic are conflicting, possibly due to the discrepancies in subject ethnicity, age, magnitude of anisometropia and different methods for measuring ocular dominance [ 8 , 13 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…reported that the nondominant eye is more myopic in the anisometropia patients with interocular SE differences greater than 2.5 D. Wang et al [ 27 ] identified the nondominant eye had a tendency of higher refraction when SE anisometropia larger than 1.75 D in adults. However, the results on which eye is more myopic are conflicting, possibly due to the discrepancies in subject ethnicity, age, magnitude of anisometropia and different methods for measuring ocular dominance [ 8 , 13 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The aniso-axial length can lead to anisometropia and challenge the choice of IOL power. The AL of the right eyes was significantly longer than the left ones, probably because of dextromanuality and right dominance of eyes [31]. However, further studies are warranted to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies support the proposition that the dominant eye is the more myopic in patients with myopic anisometropia [ 26 29 ]. The dextromanuality might contribute to the greater proportion of myopic right eyes and right dominance of eyes [ 30 ]. So, it is reasonable to find the right eyes as the longer ones in aniso-axial length individuals with the dextromanuality of Chinese.…”
Section: Discussionmentioning
confidence: 99%